Functional Outcomes of Distal Radius Fractures Undergoing Variable Angle Volar Locking Compression Plates - Khan, Danish; Hussain, Baqir (Biological and Clinical Sciences Research Journal, 2025)
Distal radius fractures are among the most common orthopedic injuries in adults, and stable fixation is essential to restore wrist function and prevent long-term disability. Variable-angle volar locking compression plates have gained popularity due to improved biomechanical stability and early mobilization. Objective: To determine the functional outcomes of distal radius fractures undergoing variable-angle volar locking compression plate management. Methods: Descriptive study. Study setting and duration: 10-11-2024 to10-05-2025 Department of Orthopaedic Surgery, Lady Reading Hospital, Peshawar. The present study was conducted on 75 patients aged 18-65 years with a distal radius fracture. Patients with open or complicated fractures were excluded. All patients underwent a variable-angle volar locking compression plate approach. The functional outcome was assessed 60 days after the procedure, using the modified Mayo wrist score. Data analysis was performed using SPSS 27, and frequency and percentages were used for functional outcomes. The chi-square test was used to evaluate the association between functional outcomes and demographics and comorbidities, with p-values < 0.05 considered significant. Results: Mean age of the cohort was 36.73 ± 11.93 years, with male gender 64.0% (n=48). The mean postoperative modified Mayo wrist score was 88.55 ± 5.82. Functional outcomes were excellent in 54.7% of cases (n=41) and good in 38.7% (n=29). Statistically significant association of fair functional outcome was found with increasing age, diabetes, hypertension, and smoking. Fewer complications were observed. Conclusion: Variable-angle volar locking compression plates for the management of distal radius fractures demonstrated excellent to good outcomes in the majority of patients. The procedure showed a favorable safety profile with minimal complications.